Ethnoscience-Based Science Learning Model to Develop Critical Thinking Ability and Local Cultural Concern for Junior High School Students in Lombok - Hikmawati Hikmawati; I Wayan Suastra; Ni Made Pujani (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to analyze the needs of students in learning science in junior high schools which will be used as a basis in designing ethnoscience-based learning models for the development of critical thinking skills and concern for students' local culture. Teachers who were used as samples of this study were 30 junior high school science teachers in Lombok. Data were collected through field observations, literature review, questionnaires, and interviews. Data were analyzed descriptively. Based on the results of data analysis, it can be concluded that: 1) There are 5 basic competencies that can be developed in ethnoscience-based learning. 2) Methods suitable for ethnoscience-based learning are investigation / experimentation, field observation, and discussion. 3) Suitable learning resources to support science learning are the natural and socio-cultural environment, textbooks, audio visuals, and the internet. 4) The assessment system suitable for ethnoscience-based science learning to develop students' critical thinking skills and local cultural awareness is non-test assessment (performance, attitudes, portfolios, products) and assessment by tests. 5) Critical thinking skills that can be developed are: Providing simple explanations, building basic skills, concluding, making further explanations, strategies and tactics. 6) Local cultural concerns that can be developed are liking local culture, introducing local culture to others, preserving local culture. 7) Conceptual model of ethnoscience-based science learning which is suitable for developing critical thinking skills and local cultural awareness includes the following steps: Engage, Explore, Explain, Elaborate, Exhibit, and Evaluate.